A World Trade Leading Index (WTLI) - Barhoumi, Karim; Ferrara, Laurent (Washington, D.C. : International Monetary Fund, 2015)
This paper develops a new monthly World Trade Leading Indicator (WTLI) that relies on nonparametric and parametric approaches. Compared to the CPB World Trade Monitor's benchmark indicator for global trade the WTLI captures turning points in global trade with an average lead between 2 and 3 months. We also show that this cyclical indicator is able to track the annual growth rate in global trade, suggesting that the recent slowdown is due in part to certain cyclical factors. This new tool can provide policy makers with valuable foresight into the future direction of economic activity by tracking world trade more efficiently.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Factor Models; Growth Rate; Leading Indicators; World Trade; WP; United States